Electrolytes Profile of Critically Ill Patients Admitted To Pediatric Intensive Care Unit (PICU) Dr. Soetomo General Hospital - Amalia Citra Octavia; Arina Setyaningtyas; Pesta Parulian Maurid Edwar (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: Fluid and electrolyte disorders can be affected by various conditions or diseases. Electrolyte disorders are often found in pediatric patients with critically ill conditions and are associated with increased morbidity also mortality that requires extra care in the Pediatric Intensive Care Unit (PICU). Objective: To describe the electrolyte profile of critically ill patients with electrolyte disorders admitted to the Pediatric Intensive Care Unit (PICU) Dr. Soetomo General Hospital. Materials and Methods: The study was conducted prospectively with a descriptive method in patients with electrolyte disorders aged 1 month – 18 years old admitted to PICU Dr. Soetomo General Hospital, Surabaya in a period from August to November 2018. Data on patient age, gender, electrolyte profile (sodium, potassium, calcium, chloride), and origin before PICU admission were recorded. Results and Discussion: From 37 patients with electrolyte disorders showed that patients were dominated by the male in 56.8% (n=21), in the age group of infants or 1-12 months old in 45.9% (n=17). Common main diagnosis in most patients were digestive system disorders in 27% (n=10), followed by central nervous system, respiratory system, kidney and cardiovascular disorders, and the origin before PICU admission were from Emergency Room (ER) in 62.2% (n=23). There were found 97 incidences of electrolyte disorders. Most frequent electrolyte disorders were hypocalcemia in 59.5% (n=22), hypokalemia in 54.1% (n=20), hyponatremia in 40.5% (n=15) and the least was hypochloremia in 35.1% (n=13). Mean serum sodium level was 138.18 ± 12.071, serum potassium level was 3.608 ± 1.2247, serum calcium level was 8.057 ± 1.9473 and serum chloride level was 101.45 ± 13.266. Conclusions:  Critically ill patients admitted in PICU tend to experience low electrolyte levels.